2021
DOI: 10.1177/1177932221999428
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics Approaches to Investigate the Gut Microbiome of COVID-19 Patients

Abstract: Over the last decade, it has become increasingly apparent that the microbiome is a central component in human well-being and illness. However, to establish innovative therapeutic methods, it is crucial to learn more about the microbiota. Thereby, the area of metagenomics and associated bioinformatics methods and tools has become considerable in the study of the human microbiome biodiversity. The application of these metagenomics approaches to studying the gut microbiome in COVID-19 patients could be one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
(149 reference statements)
1
4
0
Order By: Relevance
“…Distinct microbial signatures were identified, with the prevalence of specific OTUs in COVID-19 patients and a particular abundance of Prevotella in severe cases. This was similar to findings from a recent study [30] which highlighted a protective role of the Prevotella genus in the long-term recovery process while other investigations [31,32] reported varied results. The variation could be attributed to various factors like sample collection methods, patient demographics, or even geographic variations in microbial populations.…”
Section: Discussionsupporting
confidence: 91%
“…Distinct microbial signatures were identified, with the prevalence of specific OTUs in COVID-19 patients and a particular abundance of Prevotella in severe cases. This was similar to findings from a recent study [30] which highlighted a protective role of the Prevotella genus in the long-term recovery process while other investigations [31,32] reported varied results. The variation could be attributed to various factors like sample collection methods, patient demographics, or even geographic variations in microbial populations.…”
Section: Discussionsupporting
confidence: 91%
“…Faecalibacterium prausnitzii and Clostridium leptum had a positive correlation with neutrophil count in severe patients, as did Eubacterium rectale with IL-6 and Enterobacteriaceae with aspartate aminotransferase (AST). 14,16,17 Bacteroides ovatus, Lachnospiraceae bacterium, and Eubacterium ventriosum had a positive correlation with CD4 and CD8 lymphocytes and other T-cells. Meanwhile, Faecalibacterium prausnitzii had a positive correlation with natural killer (NK) cells and a negative correlation with Coprobacillus spp., Clostridium ramosum, and Clostridium symbiosum.…”
Section: B I O C H E M I C a L A N D I M M U N O L O G I C Modificati...mentioning
confidence: 94%
“…15 In healthy individuals, gut microbiota may offer a better understanding of individuals' susceptibility to COVID-19. 16 Changes in the standard composition and function of intestinal microbiota may predispose healthy individuals to an atypical inflammatory response, such as the one seen in COVID-19 cases. 17…”
Section: Gut Microbiota Dysbiosis Of Covid-19 Patientsmentioning
confidence: 99%
“…In contrast, the richness of beneficial bacterium was negatively correlated with the severity of the disease (Zuo et al, 2020a, b;Sehli et al, 2021). These discrepancies were independent of the antibiotic treatments, strengthening that GM might be a sufficient predictor of disease severity (Wang et al, 2016;Lai et al, 2020;Sehli et al, 2021). Population-level studies suggested that the inflammatory modulated bacteria was likely to be the signature of disease severity.…”
Section: Gm Diversity Is a Predictor Of Disease Progression In Covid-...mentioning
confidence: 99%